SEAWEED IN THE DIET OF UKRAINIANS - A STUDY OF CONSUMER PREFERENCES (Development Service Industry Management, 2024)
The article examines the relevance and prospects of using seaweed as an important source of food in the context of the growing global need for new nutrient resources. The article emphasizes the unique chemical composition of seaweed, which contains a large number of macro- and microelements, vitamins, and colloidal polymers specific to marine vegetation which ensure their high nutritional value and health properties. Given the projected growth of the global population and its nutritional needs, seaweed is presented as the potentially key resources for food security.The purpose of the study was to investigate the attitude of consumers in Ukraine towards edible seaweed, in particular, their awareness of the nutritional value of these products. For this purpose, a survey of 258 respondents was conducted. The results showed a high level of interest and consumption of seaweed among the population, sin particular, kelp and nori, and confirmed the existence of a positive attitude towards their use in the diet due to their beneficial properties, such as high protein content and low calorie content.Barriers and opportunities for increasing seaweed consumption are discussed, including the need to raise awareness of its nutritional value and expand the range of available products on the market. It also emphasizes the potential, for developing domestic seaweed production in Ukraine as a way to reduce dependence on imports and stimulate the local economy.Emphasizes the need to understand the role of seaweed in the global food supply and the possibilities of its use to ensure food security in the future.
Keywords: seaweed; kelp; consumer preferences; algal flavor; mariculture; nori; nutritionall value